1999
DOI: 10.1007/s005350050209
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a new immunochromatographic test for Helicobacter pylori IgG antibodies in elderly symptomatic patients

Abstract: FlexPack HP serum and whole blood test is a simple and reliable method for the detection of H. pylori antibodies, with 100% agreement between the serum and blood results. In the elderly symptomatic patients the sensitivity of FlexPack HP was similar to that of other serologic tests, but the specificity was relatively low, limiting its use in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
(17 reference statements)
2
13
0
Order By: Relevance
“…In general, one can expect an IgA ELISA to have lower sensitivity values than an IgG ELISA because most individuals exhibit a predominantly IgG immune response to infection with H. pylori (23). However, some investigators have found that about 2% of patients produce an IgA response in the absence of an IgG response (10,20). Furthermore, Jaskowski et al (24) showed a higher frequency of IgA-positive IgG-negative patients (38/824 cases; 7.2%) with gastrointestinal disorders suggestive of H. pylori infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, one can expect an IgA ELISA to have lower sensitivity values than an IgG ELISA because most individuals exhibit a predominantly IgG immune response to infection with H. pylori (23). However, some investigators have found that about 2% of patients produce an IgA response in the absence of an IgG response (10,20). Furthermore, Jaskowski et al (24) showed a higher frequency of IgA-positive IgG-negative patients (38/824 cases; 7.2%) with gastrointestinal disorders suggestive of H. pylori infection.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies have noted few patients with confirmed H. pylori infection and with only IgA antibodies (20,21). Aromaa A et al (22) reported that IgA antibodies and low levels of pepsinogen I increase the risk of gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, several studies 22,37 have shown that the prevalence of infection is strongly associated with age and this age‐related increase in infection falls in the elderly. Thus, the absence of serum antibodies in patients with active or previous infection seems to increase in the elderly 41,42 . It is possible that patients who had a previous infection and do not have serum antibodies are not detected as a high risk group for gastric cancer, despite the presence of severe atrophic gastritis.…”
Section: Atrophic Gastritis and Intestinal Metaplasiamentioning
confidence: 99%
“…Thus, the absence of serum antibodies in patients with active or previous infection seems to increase in the elderly. 41,42 It is possible that patients who had a previous infection and do not have serum antibodies are not detected as a high risk group for gastric cancer, despite the presence of severe atrophic gastritis. Measuring serum PG can detect patients with extensive atrophic gastritis, regardless of their H. pylori status.…”
Section: Atrophic Gastritis and Intestinal Metaplasiamentioning
confidence: 99%
“…Although anti-H. pylori IgA has been reported to be of diagnostic value in complementing IgG analysis, as some patients can be IgA positive and IgG negative (Kosunen et al, 1992;Granberg et al, 1993;Jaskowski et al, 1997;Martin-de-Argila et al, 1997;Shirin et al, 1999;Urita et al, 2004), neither the ELISA-nor the LB-based detection of IgA led to an increase in sensitivity. Although anti-H. pylori IgA has been reported to be of diagnostic value in complementing IgG analysis, as some patients can be IgA positive and IgG negative (Kosunen et al, 1992;Granberg et al, 1993;Jaskowski et al, 1997;Martin-de-Argila et al, 1997;Shirin et al, 1999;Urita et al, 2004), neither the ELISA-nor the LB-based detection of IgA led to an increase in sensitivity.…”
Section: Discussionmentioning
confidence: 99%